Homeowner Detection of and Recommendations for Mitigating Redbay Ambrosia Beetle – Laurel Wilt Disease on Redbay and Avocado Trees in the Home Landscape - Jonathan H. Crane; Jason A. Smith (EDIS)
HS1179, a 4-page illustrated fact sheet by Jonathan H. Crane and Jason A. Smith, provides homeowners with an update on redbay ambrosia beetle-laurel wilt disease in Florida, how the beetle and pathogen are spread, symptoms of infestations, and recommendations for homeowners. Includes references. Published by the UF Department of Horticultural Sciences, May 2010.